Growing and Harvesting Water. the Upbringing of the Andean Landscape Through Natural Infrastructure for Water Security - Vivas Huaccho, D. (Pontificia Universidad Catolica de Chile, 2022)
Infraestructura natural, metrpoli, centros urbanos y centros poblados superpuestos
Keywords: Rainwater harvesting; Premise; Biodiversity; Geography; Water resource management; Ecology; Environmental science; Philosophy; Biology; Epistemology; https://purl.org/pe-repo/ocde/ford#1.05.11